Preeclampsia severity and low birth weight among newborns - Sri Yekti Widadi; Siti Rissaadah; Wieda Widyatry Qarragitha; Tantri Puspita; Neng Wida (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Severe preeclampsia remains a major obstetric complication contributing to maternal and neonatal morbidity and mortality. Impaired uteroplacental perfusion associated with severe preeclampsia may restrict fetal growth and increase the risk of low birth weight (LBW). However, previous studies have reported inconsistent findings regarding this association. Purpose: To examine the relationship between severe preeclampsia and low birth weight (LBW) incidents. Method: A quantitative correlational study with a a retrospective analytical study design was conducted. A total of 97 respondents were selected through purposive sampling from 544 eligible delivery cases. Secondary data were obtained from maternal and neonatal medical records. Univariate analysis was used to describe respondent characteristics, while the Chi-square test was employed for bivariate analysis with a significance level of p<0.05. Results: The majority of mothers experienced severe preeclampsia (60.8%), and most infants were born with LBW (61.9%). Statistical analysis revealed a significant association between severe preeclampsia and LBW incidence (p=0.018). Mothers with severe preeclampsia were more likely to deliver LBW infants (43.3%) compared with those without severe preeclampsia (18.6%). Conclusion: Severe preeclampsia is significantly associated with the occurrence of LBW. These findings highlight the importance of early detection, close monitoring, and effective management of preeclampsia during pregnancy to reduce the risk of LBW and improve maternal and neonatal health outcomes.